Effect of Narrow Band Ultraviolet B Therapy versus Methotrexate on Serum Levels of Interleukin-17 and Interleukin-23 in Egyptian Patients with Severe Psoriasis - Tarek Mahmoud Elghandour; Sahar El Sayed Youssef; Dalia Gamal Aly; Mohamed Said Abd Elhameed; Mehrevan Mostafa Abdel Moneim (Dermatology Research and Practice)
Background. There is raised interest in the involvement of interleukin-(IL-)23/T-helper 17 cells (Th17) axis in the pathogenesis of psoriasis. Objectives. To compare the effect of narrow band ultraviolet B (NB-UVB) and methotrexate (MTX) therapy on serum levels of IL-17 and IL-23 in psoriatic patients. Methods. Thirty patients with severe plaque psoriasis were included: 15 patients received NB-UVB three times weekly (group I) and 15 patients received MTX 0.3 mg/kg per week (group II), both for 8 weeks. Before and after treatment, serum levels of IL-17 and IL-23 were investigated by ELISA technique and psoriasis area and severity index (PASI) was calculated. Results. After treatment, all patients showed a reduction in their PASI score, IL-17 and IL-23 serum levels with a nonsignificant difference between both therapeutic modalities (P value >0.05). A positive correlation was detected between the percent of reduction of IL-17, IL-23 and the percent of reduction of PASI score for patients receiving both treatments. No correlation was found between the percent of reduction of IL-17, IL-23 and duration of disease or age of all patients in this study. Conclusion. Interleukin-17 and IL-23 serum level may serve as a potential biomarker for predicting the prognosis and therapeutic response of NB-UVB or MTX in treating psoriasis.